THE GRADE XII STUDENTS’ ABILITY IN WRITING AN EXPLANATION TEXT AS FOUND AT SMA N 1 KECAMATAN PAYAKUMBUH - Dina Aprianti; Saunir Saun; Sitti Fatimah (Journal of English Language Teaching, 2018)
The ability to write an explanation text is the ability that must be acquired by grade XII students in senior high school that is stated in KTSP (School-based curriculum). The research was a descriptive quantitave research entitled “The Grade XII Students’ Ability in Writing an Explanation text as Found at SMA N 1 Kecamatan Payakumbuh. It was aimed at analyzing the grade XII students’ ability in writing an explanation text viewed from the generic structure and the language features. The population of the research was the grade XII students in SMA N 1 Kecamatan Payakumbuh, and the sample was 20 students of XII IPA 2 class. The students were asked to write an explanation text and their writings were analysed using the scoring rubric of the explanation text that consisting of two aspects, generic structure and language features. Based on the findings, four students were at the excellent level, seven students were at the very good level, five students were at the good level, four students were at the fair level, and there was no students in the poor level. Overall, the grade XII students’ ability in writing an explanation text as found at SMA N 1 Kecamatan Payakumbuh was at the good level.